2021
DOI: 10.3390/molecules26103013
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Phenolic Compounds in Walnut Husk and Pellicle by UPLC-Q-Orbitrap HRMS and HPLC

Abstract: Husk and pellicle as the agri-food waste in the walnut-product industry are in soaring demand because of their rich polyphenol content. This study investigated the differential compounds related to walnut polyphenol between husk and pellicle during fruit development stage. By using ultra-high performance liquid chromatography-quadrupole-orbitrap (UHPLC-Q-Orbitrap), a total of 110 bioactive components, including hydrolysable tannins, flavonoids, phenolic acids and quinones, were tentatively identified, 33 of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Compound 3 showed a [M-H] − ion at m / z 169 and two fragment ions at m / z 141 [M-H-CO] − and m / z 125 [M-H-CO 2 ] − . According to the literature data, this compound was identified as gallic acid [ 26 ]. Compound 4 produced a [M-H] − ion at m / z 343 and a base peak ion at m / z 297, corresponding to the loss of water and CO.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 3 showed a [M-H] − ion at m / z 169 and two fragment ions at m / z 141 [M-H-CO] − and m / z 125 [M-H-CO 2 ] − . According to the literature data, this compound was identified as gallic acid [ 26 ]. Compound 4 produced a [M-H] − ion at m / z 343 and a base peak ion at m / z 297, corresponding to the loss of water and CO.…”
Section: Resultsmentioning
confidence: 99%
“…Other techniques for analysis of phenolic compounds include capillary electrophoresis (CE) and micellar electro-kinetic chromatography. [22] Recent methods of analysis include ultra-high performance liquid chromatography (UHPLC) [23], ultra-high performance liquid chromatography-quadrupoleorbitrap (UHPLC-Q-Orbitrap) [24], high performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS /MS) [25], liquid chromatography coupled with electrospray-ionization triple quadrupole time-of-flight mass spectrometry (LC-ESI-QTOF-MS) and high-performance liquid chromatography-photo diode array (HPLC-PDA) [26], ESI-Ms/MS [27].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, several studies reported concentrations of the three most abundant phenolic compounds (juglone, syringic acid and ellagic acid) up to 20 times higher in the skin, compared to the seed [8]. In addition, it is reported that the concentration of phenolic compounds increases gradually from the fruiting stage to the mature stage, reporting TPC and TFC values of 52.05-279.3 mg GAE/g DW and 8.95 mg RE/g FW, respectively [5,25]. As can be seen, the presence of non-flavonoid-type phenolic compounds stands out [25].…”
Section: Skinmentioning
confidence: 99%
“…In addition, it is reported that the concentration of phenolic compounds increases gradually from the fruiting stage to the mature stage, reporting TPC and TFC values of 52.05-279.3 mg GAE/g DW and 8.95 mg RE/g FW, respectively [5,25]. As can be seen, the presence of non-flavonoid-type phenolic compounds stands out [25]. Reports stated that most of the compounds present in the walnut skin belong to hydrolyzable tannins, such as digalloyl-glucose, ellagic acid galloyl pentose or galloyl methylgalloyl dexoyhexoside isomer.…”
Section: Skinmentioning
confidence: 99%